Prognostic value of hypoxia-inducible factor-1 alpha gene polymorphism in patients with heart failure with preserved ejection fraction and obstructive sleep apnea - A. V. Yakovlev; R. S. Chernyshev; K. S. Sakhonchik; S. N. Shilov; E. V. Grakova; K. V. Kop’eva; A. T. Teplyakov; I. A. Efremov; M. S. Kessler; N. F. Yakovleva; I. A. Grebenkina (Кардиоваскулярная терапия и профилактика)
Aim. To study the associations of hypoxia-inducible factor-1 alpha (HIF-1α) gene polymorphism (rs11549465) with the clinical course of heart failure (HF) with reserved ejection fraction (HFpEF) in patients with obesity and moderate and severe obstructive sleep apnea (OSA).Material and methods. The study included 76 men with HFpEF and OSAS. Patients underwent a polysomnography, echocardiography, and a 6-minute walk test. In addition, apnea/hypopnea index was calculated, and the level of N-terminal pro-brain natriuretic peptide (NT-proBNP) was assessed. HIF1A gene polymorphisms (rs11549465) were analyzed using polymerase chain reaction. After 12-month follow-up, the clinical course of HF was assessed.Results. The T/T genotype of the HIF1A gene was associated with a high risk of HF progression (p=0,004), development of supraventricular premature beats (p=0,004) and atrial fibrillation (p=0,039). Carrying the T/T genotype was associated with severe OSA (p=0,006) and increased NT-proBNP (p=0,044), and also correlated with certain echocardiographic characteristics of myocardial remodeling.Conclusion. T/T genotype of the HIF1A gene is associated with OSA severity and increased NT-proBNP, as well as with the severity of left and right heart remodeling. The carriage of this genotype was associated with an unfavorable course of HF and an increased risk of atrial fibrillation in patients with HFpEF and OSA.